ABUNDANCE AND CONSERVATION STATUS OF AVIFAUNA IN LIMBOTO LAKE, GORONTALO - Ernikawati, Ernikawati; Puspaningrum, Dian; Panigoro, Sutan Zulham (Universitas Gorontalo, 2025)
Avifauna is a type of wildlife that can be easily found in various locations and serves as an indicator of environmental quality. Avifauna plays roles such as seed dispersal, assisting pollination, preying on other animals, and so on. It holds significant importance in wetland ecosystems. One of the most crucial ecological functions of avifauna is as a bioindicator of wetland quality, closely related to its position in the food chain. This study aims to determine the number and types of avifauna, understand the abundance of avifauna species in the waters of Limboto Lake, and identify their conservation status. The research was conducted from January to March 2025. Observations were made using the Point Count method with three (3) randomly placed points. The results identified 13 bird species belonging to 6 orders and 7 families. The percentage of species per family was highest for Passeridae at 20%, while the percentage of individual birds per family was dominated by the Ardeidae family at 47.83%. The distribution of individual birds per order was highest for the order Passeriformes with 282 individuals, and lowest for the order Charadriiformes with 11 individuals. The highest avifauna abundance was the Eurasian tree sparrow (Passer montanus) at 20.52%, indicating high criteria, while the lowest relative abundance was the Greater crested tern (Thalasseus bergii) at 1.59% and the Purple heron (Ardea purpurea) at 1.30%. The diversity index (H') was 2.14%, indicating moderate abundance criteria; evenness (E) was 0.33%, indicating a stable species distribution index; and richness (Dmg) was 1.84%, classified as a low index.